Atropine: A Cure for Persistent Post Laparoscopic Pyloromyotomy Emesis? - Cubas, Robert Frank; Longshore, Shannon; Rodriguez, Samuel; Tagge, Edward; Baerg, Joanne; Moores, Donald (Journal of Neonatal Surgery, 2016)
Background: Atropine has been used as a successful primary medical treatment for hypertrophic pyloric stenosis. Several authors have reported a higher rate of incomplete pyloromyotomy with the laparoscopic approach compared to open. In this study, we evaluated the use of atropine as a medical treatment for infants with emesis persisting greater than 48 hours after a laparoscopic pyloromyotomy. Materials and Methods: We performed a retrospective chart review of infants receiving a laparoscopic pyloromyotomy between November 1998 and November 2012. Infants with emesis that persisted beyond 48 hours postoperatively were given 0.01mg/kg of oral atropine 10 minutes prior to feeding. Infants remained inpatient until they tolerated two consecutive feedings without emesis. Results: 965 patients underwent laparoscopic pyloromyotomy; 816 (84.6%) male and 149 (15.4%) female. Twenty-four (2.5%) received oral atropine. The mean length of stay for patients who received atropine was 5.6 ± 2.6 days, an average of 3 additional days. They were discharged home with a one-month supply of oral atropine. Follow up evaluation did not reveal any complications from receiving atropine. The median follow up was 21 days. None returned to the operating room for incomplete pyloromyotomy. There were 17 (1.8%) operative complications in our series; 9 mucosal perforations, 2 duodenal perforations, and 6 conversions to open for equipment failure or poor exposure. There were 4 (0.4%) post-operative complications: 2 episodes of apnea requiring reintubation and 2 incisional hernias that required a second operation. There were no deaths. Conclusion: Oral atropine is a viable treatment for persistent emesis after a pyloromyotomy and reduces the need for a second operation due to incomplete pyloromyotomy.